Characterization of macrophages from schizophrenia patients. (December 2017) - Ormel, Paul; Mierlo, Hans; Litjens, Manja; Strien, Miriam; Hol, Elly; Kahn, René; Witte, Lot
Abstract Genetic, epidemiological andpost mortem studies have described an association between schizophrenia (SCZ) and the immune system. Microglia, the tissue-resident macrophages of the brain, not only play an essential role in inflammatory processes, but also in neurodevelopment and synapse refinement. It has therefore been hypothesized that aberrant functioning of these myeloid immune cells is involved in SCZ pathogenesis. Until now cellular research into the role of myeloid cells in SCZ has been limited to monocytes and functional assays are lacking. In this study we used monocyte-derived macrophages (mo-MΦs) as a model for macrophages and microglia in the CNS and examined two main functions: Inflammatory responses and expression and regulation of synapse refinement molecules. The expression of 24 genes involved in these key functions was assessed. Mo-MΦs were generated from 15 SCZ patients and 15 healthy controls. The cells were exposed to pro-inflammatory and anti-inflammatory stimuli (LPS, R848, IL-4 and dexamethasone), and the response was measured by qPCR and ELISA analyses. One of the genes of interest, P2RX7 that is associated with psychiatric diseases, was significantly reduced in expression after LPS stimulation in SCZ patients. None of the other assessed characteristics were different in this functional screen between mo-MΦs from SCZ patients compared to controls. Although these data suggest that overall the function of macrophages in SCZ is not impaired, further studies with larger groups that enable the possibility to study clinical subgroups and perform additional screenings to asses the full phenotype of the mo-MΦs are needed to strengthen this conclusion. Pathogenesis: Limited signs of immune cell impairment in schizophrenia Immune cells derived from schizophrenia patients exhibit similar functional characteristics to those from healthy individuals. Immunological function has repeatedly been linked to schizophrenia, yet exactly how the two interact is yet to be described. Aiming to clarify these molecular mechanisms, a team of researchers led by Paul Ormel, of the University Medical Center Utrecht, The Netherlands, took immune cells from patients and healthy individuals before assessing how the cells expressed their genetic material under normal conditions and after stimulation. For greater accuracy, the cells were changed into a cell type that resembles cells found in brain tissue. Ormel and his team found only one gene of interest that was expressed differently in cells from schizophrenia patients, which only differed during inflammatory stimulation. This is the first study investigating the function of these immune cells in schizophrenia.